Digitalization needs communication: Why software shaping is not just a technical issue - Johannes Sonnenholzner (WZB-Mitteilungen: Quartalsheft für Sozialforschung, 2023)
Organizations in all industries are faced with the task of programmming industry-specific software or having it programmed. This requires knowledge about the application area of the future software. Developers need to know what they have to program. The part of software development in which the desired software for an application area is negotiated is called software shaping. It hasn't received much attention in previous research. Johannes Sonnenholzer has taken on the topic.
Keywords: 300